Preparation method of attapulgite-based composite wave-absorbing material

CN122941353APending Publication Date: 2026-10-20HUAIYIN INSTITUTE OF TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610835309.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-10
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0004]然而目前的凹土基碳/聚苯胺复合吸波材料大多表现出阻抗匹配不佳、吸波性能不理想的问题,基于此,本发明提供了一种以凹土为基体,有机颜料为碳源,与聚苯胺协同作用的复合吸波材料的制备方法,可应用于家用电器、汽车及医疗器械等领域

Benefits of technology

[0027]本发明首先将天然颜料分子通过分子匹配技术嵌入凹土沟槽中,再通过高温碳化技术将有机颜料分子碳化制备出凹土基碳吸波材料;随后通过原位聚合法将聚苯胺沉积于凹土基碳吸波材料的表面,制备出凹土基碳-聚苯胺复合吸波材料。与现有技术相比,本发明具有如下优势:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This invention belongs to the field of composite material technology, and specifically discloses a method for preparing an attapulgite-based composite microwave absorbing material, including the following steps: (1) embedding organic pigment molecules into the groove structure of attapulgite using molecular matching technology, and then performing high-temperature carbonization treatment to obtain an attapulgite-based carbon microwave absorbing material; (2) using emulsion polymerization to deposit polyaniline on the surface of the attapulgite-based carbon microwave absorbing material to prepare an attapulgite-based carbon-polyaniline composite microwave absorbing material. In this invention, the porous structure of attapulgite forms a conductive path, promotes electromagnetic loss, and allows most electromagnetic waves to be absorbed inside the attapulgite channels. Furthermore, the carbon network inside the attapulgite further optimizes the conductive path, forming a "multi-level dielectric loss-interface polarization" composite mechanism to improve the microwave absorption performance. On the other hand, attapulgite-based carbon and polyaniline can synergistically enhance the overall microwave absorption performance of the material. The composite microwave absorbing material prepared by this invention can be applied in the fields of household appliances, automobiles, and medical devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of deep processing of natural nano-nonmetallic minerals and preparation of related new materials, and in particular to a method for preparing composite microwave absorbing materials using attapulgite, organic pigments and conductive polymers. Background Technology

[0002] With the rapid development of science and technology, especially in the fields of communication and electronics, the widespread application of electromagnetic waves has increasingly become a focus of attention. While electromagnetic waves play an important role in military, communication, and medical fields, they also bring problems such as electromagnetic interference (EMI) and electromagnetic compatibility (EMC), which not only affect the normal operation of equipment but also pose a threat to human health. Therefore, developing efficient electromagnetic wave absorbing materials to mitigate or eliminate these effects has become one of the important directions of current materials science research.

[0003] Traditional microwave absorbing materials (such as ferrite and carbon fiber) suffer from drawbacks such as high density, narrow absorption bandwidth, and insufficient environmental stability, making it difficult to meet the demands of modern equipment for lightweight design and broadband, high-efficiency absorption. Attapulgite-based carbon / polyaniline composite materials offer a new approach to solving these problems by combining the natural porous structure of attapulgite clay, the electrical conductivity of carbon materials, and the tunable electromagnetic properties of polyaniline.

[0004] However, most of the current attapulgite-based carbon / polyaniline composite microwave absorbing materials exhibit poor impedance matching and unsatisfactory microwave absorption performance. Based on this, the present invention provides a method for preparing a composite microwave absorbing material with attapulgite as the matrix, organic pigments as the carbon source, and polyaniline working synergistically, which can be applied to household appliances, automobiles, and medical devices. Summary of the Invention

[0005] To address the shortcomings of existing technologies, the present invention aims to provide a method for preparing attapulgite-based composite microwave absorbing materials. First, organic pigment molecules are embedded into attapulgite grooves using molecular matching technology. Then, the organic pigment molecules are carbonized using high-temperature carbonization technology to prepare an attapulgite-based carbon microwave absorbing material. Subsequently, polyaniline is deposited on the surface of the attapulgite-based carbon microwave absorbing material using in-situ polymerization to prepare an attapulgite-based carbon-polyaniline composite microwave absorbing material. The attapulgite-based composite microwave absorbing material prepared by the method of the present invention improves the impedance matching and attenuation capabilities of the material, enhances its microwave absorption performance, and the resulting material can be applied in fields such as household appliances, automobiles, and medical devices.

[0006] This invention is achieved through the following technical solution:

[0007] A method for preparing an attapulgite-based composite microwave absorbing material includes the following steps:

[0008] S1: After the organic pigment molecules are mixed evenly with attapulgite, they are baked in an oven to prepare attapulgite-based pigments; then the attapulgite-based pigments are calcined and carbonized under nitrogen protection to prepare attapulgite-based carbon microwave absorbing materials.

[0009] S2: The above-mentioned attapulgite-based carbon microwave absorbing material was ultrasonically dispersed in an appropriate amount of deionized water. Then, a measured amount of aniline and toluene were added to the mixture in sequence, and ultrasonic mixing was continued. The resulting mixture was then stirred and cooled in an ice-water bath. HCl solution was then added to the mixture, and stirring was continued until homogeneous. Ammonium persulfate initiator was added to the stirred mixture, and the mixture was stirred and reacted in an ice-water bath. After the reaction was completed, the mixture was centrifuged, washed, dried, and ground to prepare the attapulgite-based carbon-polyaniline composite microwave absorbing material.

[0010] A further improvement to the present invention is as follows:

[0011] The organic pigment molecule described in S1 is one or more of indigo, indigo blue, or sulphur;

[0012] Furthermore, the particle size of the attapulgite described in S1 is 20–100 nm;

[0013] Furthermore, the mass ratio of the organic pigment molecules to the attapulgite in S1 is 10-15:100.

[0014] Furthermore, the baking temperature described in S1 is 130~180℃, and the baking time is 24~48h;

[0015] Furthermore, the calcination and carbonization temperature described in S1 is 700~900℃, and the time is 2~3h.

[0016] Furthermore, the mass ratio of the attapulgite-based carbon microwave absorbing material to deionized water in S2 is 0.05–0.2:1;

[0017] Furthermore, the mass ratio of aniline to attapulgite-based carbon microwave absorbing material in S2 is 0.1–0.3:1;

[0018] Furthermore, the mass ratio of aniline to toluene in S2 is 0.3–0.6:1;

[0019] Furthermore, the molar ratio of ammonium persulfate to aniline in S2 is 0.5–2:1;

[0020] Furthermore, the concentration of the HCl solution in S2 is 0.1 mol / L, and the volume ratio of the HCl solution to deionized water is 1 to 2:10.

[0021] Furthermore, the ultrasonic dispersion time described in S2 is 20–30 min;

[0022] Furthermore, the ultrasonic mixing time described in S2 is 5–10 min;

[0023] Furthermore, the stirring and cooling time described in S2 is 5 to 10 minutes;

[0024] Furthermore, the mixing time described in S2 is 5 to 10 minutes;

[0025] Furthermore, the stirring reaction time described in S2 is 20–30 h.

[0026] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0027] This invention first embeds natural pigment molecules into attapulgite grooves using molecular matching technology, then carbonizes the organic pigment molecules using high-temperature carbonization technology to prepare an attapulgite-based carbon microwave absorbing material; subsequently, polyaniline is deposited onto the surface of the attapulgite-based carbon microwave absorbing material using in-situ polymerization to prepare an attapulgite-based carbon-polyaniline composite microwave absorbing material. Compared with existing technologies, this invention has the following advantages:

[0028] (1) In this invention, the natural pigment molecules have a quasi-planar structure, which can be molecularly matched and embedded in the grooves of the attapulgite. After high-temperature calcination, the number of pores in the attapulgite increases, in which adsorbed water, zeolite water and some crystal water are removed, and the attapulgite fibers agglomerate together, forming many micron-sized channels on the surface and inside. After high-temperature carbonization, the organic pigment molecules generate carbon black and graphene, which synergistically improve impedance matching and attenuation capabilities and are uniformly distributed in the attapulgite channels to obtain attapulgite-based carbon microwave absorbing material.

[0029] (2) In this invention, the porous structure of the attapulgite forms a conductive path, which promotes electromagnetic loss and allows most electromagnetic waves to be absorbed inside the attapulgite channels. Furthermore, the carbon network inside the attapulgite further optimizes the conductive path, forming a "multi-level dielectric loss-interface polarization" composite mechanism, which enhances the wave absorption performance.

[0030] (3) In this invention, polyaniline is deposited on the surface of attapulgite-based carbon microwave absorbing material by in-situ polymerization. The porous structure of attapulgite provides sites for uniform loading of polyaniline. Polyaniline, as a conductive polymer material, and carbonized pigment molecules, as microwave absorbing materials, work together to enhance the microwave absorption performance of the material. Attached Figure Description

[0031] Figure 1 This is a schematic diagram of the microwave absorption performance of the attapulgite-based composite microwave absorbing material prepared in Example 1;

[0032] Figure 2 This is a schematic diagram of the microwave absorption performance of the attapulgite-based composite microwave absorbing material prepared in Example 2;

[0033] Figure 3This is a schematic diagram of the microwave absorption performance of the attapulgite-based composite microwave absorbing material prepared in Example 3;

[0034] Figure 4 A schematic diagram of the microwave absorption performance of the attapulgite-based composite microwave absorbing material prepared for Comparative Example 1. Detailed Implementation

[0035] The present invention will be further described below with reference to specific embodiments, but this does not limit the present invention.

[0036] Example 1

[0037] (1) Mix 1.5 g of organic pigment indigo with 10.0 g of attapulgite and bake in an oven at 180 ℃ for 48 h to prepare attapulgite-based pigment; then place the attapulgite-based pigment in a protective atmosphere furnace, introduce nitrogen gas for protection, and calcine and carbonize at 800 ℃ for 2 h to prepare attapulgite-based carbon microwave absorbing material.

[0038] (2) Take 5.0 g of the above-mentioned attapulgite-based carbon microwave absorbing material and ultrasonically disperse it in 100 ml of deionized water for 30 min. Then add 0.15 g of aniline and 2.5 g of toluene to it and continue ultrasonication for 5 min. Then add 15 ml of 0.1 mol / L HCl solution to the mixture and continue stirring for 5 min. Add 0.90 g of initiator APS to the stirred mixture and stir the reaction under ice water bath for 24 h. Centrifuge, wash, dry and grind to prepare attapulgite-based carbon-polyaniline composite microwave absorbing material.

[0039] The microwave absorption performance of the prepared attapulgite-based composite microwave absorbing material is as follows: Figure 1 As shown.

[0040] Depend on Figure 1 It can be seen that the attapulgite-based carbon-polyaniline composite material prepared in Implementation Method 1 has good wave absorption performance. When the coating thickness is 3.5 mm, its minimum reflection loss can reach -11 dB, and its reflection loss is less than -5 dB within the test frequency range, with an absorption bandwidth of 10 GHz.

[0041] Example 2

[0042] (1) Mix 2.0 g of organic pigment indigo with 10.0 g of attapulgite evenly, and bake in an oven at 180 ℃ for 48 h to prepare attapulgite-based pigment; then place the attapulgite-based pigment in a protective atmosphere furnace, introduce nitrogen gas for protection, and calcine and carbonize at 800 ℃ for 2 h to prepare attapulgite-based carbon microwave absorbing material.

[0043] (2) Take 5.0 g of the above-mentioned attapulgite-based carbon microwave absorbing material and ultrasonically disperse it in 100 ml of deionized water for 30 min. Then add 0.30 g of aniline and 2.5 g of toluene and continue ultrasonication for 5 min. Then add 15 ml of 0.1 mol / L HCl solution to the mixture and continue stirring for 5 min. Add 0.90 g of initiator APS to the stirred mixture and stir the reaction under ice water bath for 24 h. Centrifuge, wash, dry and grind to prepare attapulgite-based carbon-polyaniline composite microwave absorbing material.

[0044] The microwave absorption performance of the prepared attapulgite-based composite microwave absorbing material is as follows: Figure 2 As shown.

[0045] Depend on Figure 2 It can be seen that the attapulgite-based carbon-polyaniline composite material prepared in Embodiment 2 has good microwave absorption performance. When the coating thickness is 3.5 mm, its minimum reflection loss can reach -14 dB, and its reflection loss is less than -5 dB in the test frequency range, with an absorption bandwidth of 10 GHz. When the coating thickness is 2.0 mm, its reflection loss is also less than -5 dB in the test frequency range, showing excellent microwave absorption performance.

[0046] Example 3

[0047] (1) After mixing 2.0 g of organic pigment Sudan with 10.0 g of attapulgite evenly, the mixture was placed in an oven at 180 ℃ and baked for 48 h to prepare attapulgite-based pigment; then the attapulgite-based pigment was placed in a protective atmosphere furnace, nitrogen gas was introduced for protection, and carbonized at 700 ℃ for 2 h to prepare attapulgite-based carbon microwave absorbing material.

[0048] (2) Take 5.0 g of the above-mentioned attapulgite-based carbon microwave absorbing material and ultrasonically disperse it in 100 ml of deionized water for 30 min. Then add 0.45 g of aniline and 2.5 g of toluene to it and continue ultrasonication for 5 min. Then add 15 ml of 0.1 mol / L HCl solution to the mixture and continue stirring for 5 min. Add 0.90 g of initiator APS to the stirred mixture and stir the reaction under ice water bath for 24 h. Centrifuge, wash, dry and grind to prepare attapulgite-based carbon-polyaniline composite microwave absorbing material.

[0049] The microwave absorption performance of the prepared attapulgite-based composite microwave absorbing material is as follows: Figure 3 As shown.

[0050] Depend on Figure 3It can be seen that the attapulgite-based carbon-polyaniline prepared in Embodiment 3 has excellent microwave absorption properties. When the coating thickness is 2.0 mm, the reflectivity of the composite material is less than -5 dB in the test frequency range. When the coating thickness is 3.5 mm, the minimum reflection loss of the composite material reaches -15 dB, and the reflectivity is also less than -5 dB in the test frequency range, indicating that the composite material is a wide-absorption microwave absorbing material.

[0051] Comparative Example 1

[0052] The difference between this comparative example and Example 1 is that no organic pigments are added; other operations are largely the same as in Example 1, and will not be repeated here. The microwave absorption performance of the prepared attapulgite-based microwave absorbing material is as follows: Figure 4 As shown.

[0053] Depend on Figure 4 It can be seen that the attapulgite-based polyaniline prepared in Comparative Example 1 has poor wave absorption performance. In the range of 2-12 GHz, when the coating thickness is 1.5-3.5 mm, the reflectivity of this composite material is greater than -5 dB in the test frequency range, indicating poor wave absorption performance.

[0054] The above description of the embodiments is only for illustrating the technical concept and features of the present invention. Its purpose is to enable those skilled in the art to understand the content of the present invention and implement it accordingly. Those skilled in the art can obviously easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative effort. Therefore, the above embodiments should not be used to limit the scope of protection of the present invention. All improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be covered within the scope of protection of the present invention.

Claims

1. A method for preparing a attapulgite-based composite microwave absorbing material, characterized in that, Includes the following steps: S1: After the organic pigment molecules are mixed evenly with attapulgite, they are baked in an oven to prepare attapulgite-based pigments; then the attapulgite-based pigments are calcined and carbonized under nitrogen protection to prepare attapulgite-based carbon microwave absorbing materials. S2: The above-mentioned attapulgite-based carbon microwave absorbing material was ultrasonically dispersed in an appropriate amount of deionized water. Then, a measured amount of aniline and toluene were added to the mixture in sequence, and ultrasonic mixing was continued. The resulting mixture was then stirred and cooled in an ice-water bath. HCl solution was then added to the mixture, and stirring was continued until homogeneous. Ammonium persulfate initiator was added to the stirred mixture, and the mixture was stirred and reacted in an ice-water bath. After the reaction was completed, the mixture was centrifuged, washed, dried, and ground to prepare the attapulgite-based carbon-polyaniline composite microwave absorbing material.

2. The method for preparing a attapulgite-based composite microwave absorbing material according to claim 1, characterized in that: The organic pigment molecule described in S1 is one or more of indigo, indigo blue, or sulphur; And / or, the particle size of the attapulgite is 20–100 nm.

3. The method for preparing a attapulgite-based composite microwave absorbing material according to claim 1, characterized in that: The mass ratio of the organic pigment molecules to the attapulgite in S1 is 10-15:

100.

4. The method for preparing a attapulgite-based composite microwave absorbing material according to claim 1, characterized in that: The baking temperature described in S1 is 130~180℃, and the time is 24~48h; And / or, the calcination and carbonization temperature is 700~900℃, and the time is 2~3h.

5. The method for preparing a attapulgite-based composite microwave absorbing material according to claim 1, characterized in that: The mass ratio of the attapulgite-based carbon microwave absorbing material to deionized water in S2 is 0.05–0.2:1; And / or, the mass ratio of aniline to attapulgite-based carbon microwave absorbing material is 0.1 to 0.3:1; And / or, the mass ratio of aniline to toluene is 0.3 to 0.6:1; And / or, the molar ratio of ammonium persulfate to aniline is 0.5 to 2:1; And / or, the concentration of the HCl solution is 0.1 mol / L, and the volume ratio of the HCl solution to deionized water is 1 to 2:

10.

6. The method for preparing a attapulgite-based composite microwave absorbing material according to claim 1, characterized in that: The ultrasonic dispersion time described in S2 is 20–30 min; And / or, the ultrasonic mixing time is 5 to 10 minutes; And / or, the stirring and cooling time is 5 to 10 minutes; And / or, the mixing time is 5 to 10 minutes; And / or, the stirring reaction time is 20 to 30 hours.